Dangerous Spaces, Dangerous Liaisons: Performance Arts on and of the U.S./Mexico Border - Kirsten F. Nigro (Studies in 20th & 21st Century Literature, 2008)
This essay will consider the performative arts on the border, ranging from script-based plays to performance pieces in urban spaces and public installation pieces. These will be analyzed according to their focus on 1) the plight of the illegal immigrant; 2) the violence that has become a daily factor in the lives of border citizens; and 3) the symbolic efforts to make a sacred space out of one as seemingly unsacred as the border; and if not a sacred space, one that is more transparent and hopefully, less dangerous and threatening.
Keywords: performance arts; urban spaces; public installation; illegal immigration; border citizens; border life; violence; sacred; U.S./Mexico border